2018
DOI: 10.1111/ene.13649
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological study of critical illness polyneuropathy and myopathy in mechanically ventilated children; additional aspects in paediatric critical illness comorbidities

Abstract: Critically ill children frequently develop CIP/CIM, mostly of axonal polyneuropathy pattern, which compromises rehabilitation and recovery and is associated with a number of comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
10
0
2
Order By: Relevance
“…Paediatric patients can also develop CIP or CIM, although the incidence here is potentially lower than that in adult patients [117].…”
Section: Pathophysiology Of Weaning Failurementioning
confidence: 99%
“…Paediatric patients can also develop CIP or CIM, although the incidence here is potentially lower than that in adult patients [117].…”
Section: Pathophysiology Of Weaning Failurementioning
confidence: 99%
“…Prevalence of ICU-acquired weakness varies widely with the studied patient population and risk factors, the timing of assessment, the methods used for diagnosis, and inconsistent accounting for patients' pre-hospital muscle function or overall functional status (often overlooking agerelated frailty) [4,6,[9][10][11][12]. A systematic review reported a median prevalence of 43% (interquartile range 25-75%) over 31 studies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our results support that ICU-AP frequency was more than one third of conscious patients and the most important factor for ICU paresis was mechanical ventilator. ICU-AP frequency has reported between 25% and 55% in literature (1,2,(10)(11)(12)(13)(14). Cramer mentioned that change in electrophysiological findings (sudden decrease in compound muscle action potential amplitude) indicating the development of CINM was monitored in higher than 65% of patients in one study (15).…”
Section: Discussionmentioning
confidence: 99%